How the master’s level is implemented in internships within master’s programmes — exploring the views of students, clinicians, and educators in midwifery and public health nursing - Jürgen Kasper; Turid Kristin Bigum Sundar; Lisbeth Valla; Anne Marie Lilleengen; Anne Grete Rydtun Haug; Kjersti Engen Marsdal; Iren Borgen; Victoria Telle Hjellset (BMC Medical Education, 2024)
Abstract In the course of worldwide attempts at the academisation of professional education and the Bologna process, nursing education has become both bachelor’s and master’s programmes at colleges, polytechnics, and universities. We investigated how a master’s level in internships is conceptionalised by the involved parties. Our focus was on Norwegian master’s education programmes in two different health professions, midwifery and public health nursing. The study also aimed at providing a better understanding of barriers and facilitators of realising the master’s level in internships. Using the Theory of Planned Behaviour as a theoretical and methodological framework, we conducted individual in depth interviews with representatives of all involved parties (supervisors, students, university teachers, and clinic managers). After content analysing the interview data, we held focus group meetings aiming to confirm the findings from the first part of the study. The findings reveal a controversial debate over the necessity of a master’s level education and the challenges participants reported from their attempts to implement the master’s level into student internships. The main result is the lack of consensus on the role of internships within a master’s programme and on how students, practise supervisors, and educational institutions should collaborate on this issue. Various assumptions about the roles, accountability, and professional functions of a master’s student during an internship have been distilled into five distinct models. Instead of comparing and ranking these models, their mere coexistence is discussed as an obstacle to implementing advanced nursing practise. Recommendations are provided to help resolve this confusion.